PENGARUH TINGKAT DISIPLIN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS XI DI SMAN 05 PONTIANAK UTARA - Nurul Ulfa; Aminuyati Aminuyati; Achmadi Achmadi (Universitas Tanjungpura, 2021)
AbstrackThis research aims to find out (1) The influence of student learning discipline levels in economics lessons on the learning outcomes of students of class XI IIS SMAN 05 North Pontianak; (2) The influence of motivation to learn in economics lessons on the learning outcomes of students of class XI IIS SMAN 05 North Pontianak; and (3) The influence of the level of discipline and motivation to study together on the economic learning outcomes of students in class XI majoring in IIS SMAN 05 North Pontianak. This study included an ex-post-facto type of research with a research population of 135 students of class XI Major IIS SMAN 05 North Pontianak. The study subjects were taken as many as 33 students of grades XI 1 IIS, XI 2 IIS, XI 3 IIS, XI 4 IIS used as subjects in research instrument trials. The data collection using questionnaire methods, documentation, and google form. The data analysis techniques used are simple regression analysis techniques and double regression analysis. The results of the study are: (1) The disciplinary level has a positive influence and significance on the economic learning outcomes of students of class XI Major IIS SMAN 05 North Pontianak; (2) The learning motivation has a positive and significant influence on the economic learning outcomes of students of class XI Major IIS SMAN 05 North Pontianak; (3) The level of discipline and motivation to learn together has a positive and significant influence on the results of economic learning class XI Department IIS SMAN 05 North Pontianak with a value of Ry1.2 = 0.999> 0.355 rtable and a score of Fcount 7,100 > Ftable (3.1).Keywords: Level of Discipline, Learning Motivation, Economic Learning Outcomes PENDAHULUA